Observation of fast and slow interatomic Coulombic decay in argon dimers induced by electron-impact ionization - Ren, Xueguang; Miteva, Tsveta; Gokhberg, Kirill; Kuleff, Alexander I.; Cederbaum, Lorenz S. (Physical review, 2017)
We investigate the interatomic Coulombic decay (ICD) in argon dimers induced by electron-impact ionization (E0=90eV) using a multiparticle coincidence experiment in which the momentum vectors and, consequently, the kinetic energies for electrons and fragment ions are determined. The signature of the ICD process is obtained from a correlation map between ejected electron energy and kinetic energy release (KER) for Ar++Ar+ fragment ions where low-energy ICD electrons can be identified. Furthermore, two types of ICD processes, termed fast and slow interatomic decay, are separated by the ICD initial-state energies and projectile energy losses. The dependence of the energies of emitted low-energy ICD electrons on the initial-state energy is studied. ICD electron energy spectra and KER spectra are obtained separately for fast and slow decay processes where the KER spectra for the slow decay channel are strongly influenced by nuclear motion. The KER and ICD electron energy spectra are well reproduced by ab initio calculations.
Gesehen am 16.05.2018